Coronavírus e o agronegócio brasileiro: impactos da pandemia na dinâmica de consumo e no fornecimento dos alimentos - Riker, Joabe Cota (Brasil, 2022)
Since the beginning of the pandemic, Brazil has already faced “three waves” of the disease in which, in this context, the coronavirus exposed vulnerable populations, enhancing social inequalities. In view of this, the question is: what were the impacts of the pandemic on the supply and on the dynamics of food consumption in light of the Sustainable Development Goal - SDG nº 2 for the eradication of hunger and sustainable agriculture in Brazil? The general objective is to demonstrate what were the main actions adopted in Brazil to face the negative effects of the health crisis caused by the spread of COVID-19 in Brazilian agribusiness and its impacts on regional agricultural value chains, to understand to what extent the spread of the virus and the measures to stop the movement of people economically affected the Brazilian agricultural sector and the relationship with food insecurity of families. Throughout the work, the inclusion of specific repair policies became evident; the impacts on the Brazilian agricultural sector with effects on family farming; and the risks to food security from the perspective of the Sustainable Development Goal – SDG 2 of the United Nations – UN. For the methodological procedures, bibliographic and documental research was considered, aiming at Content Analysis for the treatment of data. The results showed a strong growth trend in the sector, concluding that there are very positive consequences of this success in the economy, although with some negative effects in the increase of social inequalities.